CONCEPT OF SELF-DEVELOPMENT OF STUDENTS IN EDUCATIONAL AND INFORMATION ENVIRONMENT OF THE HIGHER MILITARY EDUCATIONAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2022)
The article is concerned with the conception of cadets' self-development in teaching-informative environment of higher military educational establishes organized normation of teaching-educational process, intensification of teaching-informative activity differentiation, individualization, personification of training.
Keywords: self-development; cadet; teaching-informative enviroment of higher military educational establishment